2020
DOI: 10.1111/jce.14336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nurse‐led limited risk factor modification program on arrhythmia outcomes in patients with atrial fibrillation undergoing catheter ablation

Abstract: Background:We have previously demonstrated the feasibility of a nurse-led risk factor modification (RFM) program for improving weight loss and obstructive sleep apnea (OSA) care among patients with atrial fibrillation (AF).Objective: We now report its impact on arrhythmia outcomes in a subgroup of patients undergoing catheter ablation.Methods: Participating patients with obesity and/or need for OSA management (high risk per Berlin Questionnaire or untreated OSA) underwent in-person consultation and monthly tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The results of this study did not support a causal pathway between SDB, in general, and AF, after accounting for BMI. There is a growing body of observational [ 8 , 9 , 10 , 11 ] and clinical trial evidence [ 12 , 13 ] suggesting a possible lack of direct causal association between OSA, the most common form of SDB, and AF. A recent, small RCT failed to show a benefit of CPAP against AF recurrence after cardioversion in patients with persistent AF [ 12 ], though the results should be interpreted with caution as recruitment targets were not met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study did not support a causal pathway between SDB, in general, and AF, after accounting for BMI. There is a growing body of observational [ 8 , 9 , 10 , 11 ] and clinical trial evidence [ 12 , 13 ] suggesting a possible lack of direct causal association between OSA, the most common form of SDB, and AF. A recent, small RCT failed to show a benefit of CPAP against AF recurrence after cardioversion in patients with persistent AF [ 12 ], though the results should be interpreted with caution as recruitment targets were not met.…”
Section: Discussionmentioning
confidence: 99%
“…Some large observational studies have failed to demonstrate an association between OSA and AF that is independent of other cardiovascular risk factors [ 8 , 9 ]. Furthermore, the presence of OSA, and its treatment with CPAP, have recently been shown not to impact arrhythmia outcomes following ablation [ 10 , 11 ] or cardioversion [ 10 ]. Early and small RCTs have shown no impact of CPAP on time to AF recurrence post-cardioversion [ 12 ] or differences in AF burden or quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otra rama importante de las funciones de la enfermera experta en FA es el manejo de los factores de riesgo modificables que pueden provocar o intensificar los episodios de FA 31 . Es importante identificar aquellos pacientes con obesidad o AOS para poder establecer un tratamiento adecuado para su control 32 . Por lo tanto, es importante establecer circuitos asistenciales para que los pacientes que cumplan estas características sean valorados por la unidad del sueño 33 o el equipo de cirugía bariátrica ya que su control y mejoría, asegura los resultados positivos de la ablación de FA a largo plazo [34][35][36] .…”
Section: Discussionunclassified
“…61 Consistent with these findings, no differences were reported in freedom from arrhythmia after ablation among AF patients receiving standard care or weight and obstructive sleep apnoea management. 62 Finally, a large retrospective study of 30 188 patients with sleep-disordered breathing (obstructive sleep apnoea or central sleep apnoea) showed that time to recurrent AF after cardioversion or ablation was not influenced by continuous positive airway pressure treatment (hazard ratio 1.01 (95% confidence interval 1.00 to 1.02)). 63 The conflicting evidence for the effects of obstructive sleep apnoea on AF risk might be partly explained by the confounding effects of concurrent obesity.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%